Revamping the Environment for National Development: A Lexico-Semantic Reading of Niyi Osundare’s The Eye of the Earth - OKOH, MARY ENWELIM-NKEM (International Journal of Language and Literary Studies, 2021)
Environmental poetry is relatively young in the literature of the Nigerian literary writers and critics. Literary scholars of an earlier generation before Osundare – Soyinka, Okigbo, and Okara have dwelt more on the themes and language of cultural heritage, cultural conflicts, colonial and post-colonial political, socio-economic and religious issues. They barely scratched around the themes of environment and ecology. More so, their language may be adjudged obscure and esoteric. Therefore, the present study engages in the exploration of Osundare’s innovative and full-scale venture into pivotal issues of the environment that have become of utmost concern nationally and internationally in contemporary times. Also of interest in this study is Osundare’s efforts to redefine the diction of Nigerian poetry to reach a wider audience. Osundare’s poetry collection, The Eye of the Earth is our focal text. It has been observed that critical studies on this collection are largely centered on literary interpretations. Lexico-semantic exploration of this collection can be considered inadequate, which necessitated the present study to strike a balance in deciphering Osundare’s language and thematic preoccupations. This study is anchored on systemic functional linguistics (SFL) and eco-criticism theory with insights from lexical-semantic theory. Poems of environmental background are purposively selected from the collection. The study reveals Osundare’s tactical manipulation of “common” language in exposing man’s pernicious activities in the natural environment. In a similar manipulative skill in language use, the study unveils consequential roles imperative for a man to obviate his adverse activities on nature in order to achieve development at different spheres of life.